2017
DOI: 10.1136/bmjopen-2017-016415
|View full text |Cite
|
Sign up to set email alerts
|

How health service delivery guides the allocation of major trauma patients in the intensive care units of the inclusive (hub and spoke) trauma system of the Emilia Romagna Region (Italy). A cross-sectional study

Abstract: ObjectiveTo evaluate cross-sectional patient distribution and standardised 30-day mortality in the intensive care units (ICU) of an inclusive hub and spoke trauma system.SettingICUs of the Integrated System for Trauma Patient Care (SIAT) of Emilia-Romagna, an Italian region with a population of approximately 4.5 million.Participants5300 patients with an Injury Severity Score (ISS) >15 were admitted to the regional ICUs and recorded in the Regional Severe Trauma Registry between 2007 and 2012. Patients were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…According to such estimated caseloads, a plan of action was settled on clustering all urgent neurosurgical activities (mainly trauma and vascular) among only 3 centers (Niguarda, Brescia, and Varese), which were chosen based on geographical criteria as well as their receptive capacity, creating a hub-and-spoke scheme. 2 Only one other hospital for the entire region (Fondazione IRCCS Istituto Neurologico Besta) was identified to deal with nondeferrable tumor cases.…”
Section: The Hub-and-spoke Systemmentioning
confidence: 99%
“…According to such estimated caseloads, a plan of action was settled on clustering all urgent neurosurgical activities (mainly trauma and vascular) among only 3 centers (Niguarda, Brescia, and Varese), which were chosen based on geographical criteria as well as their receptive capacity, creating a hub-and-spoke scheme. 2 Only one other hospital for the entire region (Fondazione IRCCS Istituto Neurologico Besta) was identified to deal with nondeferrable tumor cases.…”
Section: The Hub-and-spoke Systemmentioning
confidence: 99%
“…The HSM has been mainly applied to manage the acute phase of neurological diseases (Demaerschalk, 2013; Chieregato et al , 2017; Gadhia, 2018). In particular, it has been demonstrated that an innovative HSM using a telestroke network may increase the number of patients discharged home and reduce the costs borne by the network hospitals (Demaerschalk et al , 2013; and 2018)…”
Section: Background and Rationalementioning
confidence: 99%
“…Nonetheless, a recent Italian study reported that about 12% of all severe TBI patients were admitted to the nearest hospital without neurosurgery capabilities (no-NSH) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%